EFEKTIVITAS RELAKSASI NAFAS DALAM DAN AROMATERAPI LAVENDER TERHADAP KECEMASAN MAHASISWA MENGHADAPI UJIAN SKILL LABORATORY - Lina Triwahyuni; Ririn Muthia Zukhra; Jumaini Jumaini (Jurnal Pendidikan Kesehatan, 2021)
Facing the laboratory skill test is one of the causes of anxiety. Deep breath relaxation and aromatherapy lavender are a combination intervention that effectively reduces anxiety. The purpose of this study was to determine the effect of deep breath relaxation and aromatherapy lavender on student anxiety facing the laboratory skill test at the Faculty of Nursing, University of Riau. The research method was used quasy experiments with the pretest posttest with control group design. The study sample amounted to 34 people divided into 17 experimental groups and 17 control groups using Simple Random Sampling Techniques. The instrument uses a standardized questionnare S AI or State Anxiety Inventory from Y 1 which measures the level of anxiety with a score of 1 until 80. The analysis used is univariate and bivariate analysis using the Dependent Sample T test and Independent Sample T test. The results showed that average before intervention was 50,06 and after intervenstion was 31,18. Statistically there is an effect of deep breath relaxation and aromatherapy lavender can be used to reduce level of anxiety in student facing laboratory skill test with P value 0,000 less than P 0.05.